Transformasi Pembelajaran pada Jurusan Perhotelan Tingkat SMK di Bali Melalui Aplikasi Simulasi Digital Berbasis Game - I Made Suandana Astika Pande (Journal of Innovation Research and Knowledge, 2026)
Vocational hospitality education in Bali's Sekolah Menengah Kejuruan (SMK) plays a strategic role in supplying skilled labor for the global tourism industry. However, the effectiveness of learning is often hindered by limited physical practice facilities and a lack of interactive teaching methods, creating a gap between students' competencies and industry standards. This study aims to address this problem by developing "VocaHotel," a game-based digital simulation application that offers an immersive and realistic virtual practice experience focused on the Front Office division. The application was developed using the Game Development Life Cycle (GDLC) method, which ensured the development process proceeded systematically from initiation to release. Functional testing was carried out using the blackbox method, confirming that all system features, including character/role selection, non-player character (NPC) dialogue and movement, and item-spawning mechanics, worked as expected. A usability test was then conducted with 48 hospitality students using a five-point Likert scale, yielding an overall feasibility score of 72.42%, categorized as "Good." The highest-rated aspect was student learning motivation (76.25%), confirming that the gamification elements effectively increased students' enthusiasm compared to conventional methods, while the lowest-rated aspect, character navigation (67.92%), indicates a need for improved control tutorials. VocaHotel has been finalized and published on the Google Play Store as a companion learning medium. These findings suggest that VocaHotel offers a concrete, low-cost alternative for overcoming practical-facility constraints, improving graduates' readiness for the hospitality industry in Bali and beyond.